VALIDITY OF INTEGRATED SCIENCE MODULES BASED ON LOCAL WISDOM TO TRAIN SCIENCE LITERACY AND CULTURAL LITERACY - Dea Irna Fatmawati; Ahmad Muhlisin; Siswanto Siswanto (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
Students' science literacy and cultural literacy skills are still relatively low because the learning process generally relies on teaching materials that do not integrate scientific concepts with local wisdom. To address this issue, this study aims to develop an integrated science module based on Nglipoh pottery crafts and traditional spinning top games as an effort to train students' science and cultural literacy skills. This study uses the Research and Development (R&D) method with a 3-D model (define, design, develop) combined with the RIAS (Reading, Identification, Analysis, Self-reflection) learning model. Data were collected through unstructured interviews, literature reviews, and expert validation questionnaires. The validation instruments were given to four validators who assessed the content, presentation, language, and graphics of the module. The validation results showed that the module scored 90% in terms of graphics and 91.02% in terms of content, presentation, and language, thus falling into the highly valid category. Thus, the Nglipoh pottery-based integrated science module and traditional spinning top game are declared suitable for use as teaching materials to help train of science literacy and cultural literacy among junior high school students.